2004
DOI: 10.1139/y03-131
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the enterohepatic recirculation of bile acids in rats after exposure to ionizing radiation

Abstract: The aim of this work was to study acute alterations of the enterohepatic recirculation (EHR) of bile acids 3 days after an 8-Gy radiation exposure in vivo in the rat by a washout technique. Using this technique in association with HPLC analysis, the EHR of the major individual bile acids was determined in control and irradiated animals. Ex vivo ileal taurocholate absorption was also studied in Ussing chambers. Major hepatic enzyme activities involved in bile acid synthesis were also measured. Measurements of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
5
1
1
Order By: Relevance
“…Problems such as anorexia, weight loss 47) and visceral tissue damage were not found, although they have been described with stronger external gamma irradiation. 48) Also, our study did not show a body weight increase as described in case of higher cumulated irradiation (6 Gy) at low-dose rate in rodents exposed during the same duration (9 months).…”
Section: Discussionmentioning
confidence: 92%
“…Problems such as anorexia, weight loss 47) and visceral tissue damage were not found, although they have been described with stronger external gamma irradiation. 48) Also, our study did not show a body weight increase as described in case of higher cumulated irradiation (6 Gy) at low-dose rate in rodents exposed during the same duration (9 months).…”
Section: Discussionmentioning
confidence: 92%
“…Previously reported studies have shown that radiation causes bile salt malabsorption in the intestine due to terminal ileal damage (6, 7). The metabolomics results above also indicated altered levels of bile acids in feces after irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…This is in accordance with a previously reported study in rats showing an increase in conjugated bile acids postirradiation as the result of reduced capacity of the microbiome to deconjugate and desulphate bile acids (29). In addition, a separate study concluded that bile acid levels increased as early as 24 h postirradiation and remained persistently high three days after exposure (7). Under physiological conditions, 90% of bile acids are reabsorbed by the gut by the highly efficient enterohepatic recirculation system (38), which may indicate that the radiation-induced bile acid increases in the colonic contents is due to the reduction of intestinal absorption caused by radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La régénération de l'intestin par les CSM peut-elle prévenir les effets néfastes, induits par l'irradiation, sur d'autres tissus du tube digestif tel que le foie ? Nous avons montré que l'irradiation induit une altération de l'intégrité hépatique, avec une élévation du taux des transaminases, associée à une augmentation du nombre de cellules lysées autour des vaisseaux et des canaux biliaires (Scanff et al 2004 ;Souidi et al 2007). L'injection de CSM permet le retour à la normale.…”
Section: Utilisation Des Csm De La Moelle Osseuse Dans Le Traitement unclassified